Factors related to cervical cancer and human papilloma virus awareness among rural women of southern Bangladesh: A cross-sectional study - Sattyajit Datta; Syed Baqui Billah; Anik Halder; Tarequr Rahman (Elsevier, 2024)
Introduction: Cervical cancer is an important public health issue in Bangladesh. Despite government efforts, the awareness and healthcare utilization in rural areas are inadequate. Methodology: This cross-sectional study was conducted in six districts of Barishal division over 997 respondents aged 15-64 years. The demographic variables, accessibility to healthcare, vaccination status, awareness of HPV causing cervical cancer, and knowledge of the HPV vaccine were recorded through a structured questionnaire. T-test for univariate and chi-square test for bi-variate analysis were used. Logistic regression was used to determine factors associated with awareness. Results: Most of the participants were SSC passed (45.3%), unemployed (54.4%), and married (74.4%). While 83.5% were aware of cervical cancer, only 3.3% knew about HPV's role. The majority (96.2%) had never been tested for HPV, albeit 79.5% knew about the vaccine, and only 2.45% were vaccinated. Knowledge levels were low, with only 1.4% demonstrating sound knowledge, mostly associating with higher income, residing closer to healthcare facilities, and being married. Bhola district participants had highest level of awareness, and the lowest was in Pirojpur. Education level was positively correlated with knowledge, with graduates being most aware. Logistic regression showed education, marital status, willingness to vaccinate daughters, and district were significantly related with better awareness, while income, distance, and age did not. Conclusion: Mass education and awareness campaigns may improve the awareness level in rural community.